2018
DOI: 10.1038/s41401-018-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin-6′-O-benzene sulfonate alleviates collagen-induced arthritis in mice by downregulating BAFF-TRAF2-NF-κB signaling: comparison with biological agents

Abstract: Paeoniflorin-6′-O-benzene sulfonate (CP-25) is a new ester derivative of paeoniflorin with improved lipid solubility and oral bioavailability, as well as better anti-inflammatory activity than its parent compound. In this study we explored whether CP-25 exerted therapeutic effects in collagen-induced arthritis (CIA) mice through regulating B-cell activating factor (BAFF)-BAFF receptors-mediated signaling pathways. CIA mice were given CP-25 or injected with biological agents rituximab or etanercept for 40 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Peripheral blood B cells are mainly derived from CD19 + IgM + IgD + type II transitional B cells (Loder et al, 1999). A previous study in our laboratory has shown that etanercept could reduce the percentage of CD19 + total B cells, CD19 + CD27 + memory B cells, and CD19 − CD27 + CD138 + plasma B cells in CIA mice (Shu et al, 2019). In order to investigate whether etanercept has an effect on the differentiation of B cells, we further designed a series of animal experiments.…”
Section: Discussionmentioning
confidence: 90%
“…Peripheral blood B cells are mainly derived from CD19 + IgM + IgD + type II transitional B cells (Loder et al, 1999). A previous study in our laboratory has shown that etanercept could reduce the percentage of CD19 + total B cells, CD19 + CD27 + memory B cells, and CD19 − CD27 + CD138 + plasma B cells in CIA mice (Shu et al, 2019). In order to investigate whether etanercept has an effect on the differentiation of B cells, we further designed a series of animal experiments.…”
Section: Discussionmentioning
confidence: 90%
“…Many basic and preclinical studies suggested that paeoniflorin has potent anti-inflammatory, antitumor, and anti-hyperglycemia properties ( 16 19 ). Paeoniflorin exerts therapeutic effects on collagen-induced arthritis ( CIA ) rats via mediating Akt/mTOR signaling pathway and represses antibodies production from B cells ( 20 ). In addition, paeoniflorin imposes strong inhibition effect on mTOR-hypoxia inducible factor-1a pathway, leading to a reduction of alpha-smooth muscle actin (a-SMA) and collagen protein production and alleviation of liver fibrosis ( 21 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…After the onset of inflammation, the AI of the CIA mice in each group was evaluated once every 3 days as follows: 0, no signs of arthritis; 1, swelling and/or redness of the paw or one digit; 2, two joints involved; 3, more than two joints involved; and 4, severe arthritis of the entire paw and all digits. All feet were measured, the maximum score value of each mouse was 16 [21].…”
Section: Evaluation Of Arthritismentioning
confidence: 99%
“…The ankle joints of mice were immersed in 10% formalin, then decalcified and paraffinembedded [21]. The sections (5 mm) were stained with hematoxylin and eosin.…”
Section: Histological Examinationmentioning
confidence: 99%